IMAGING DIAGNOSIS—PULMONARY ALVEOLAR PROTEINOSIS IN A DOG. Issue 6 (21st April 2013) - Cummings, Annelise C.; Spaulding, Kathy A.; Scott, Katherine D.; Edwards, John F.
Abstract : A young dog was presented for cyanosis and right heart failure. Radiographic and CT characteristics included right heart/pulmonary artery enlargement, hepatomegaly, abdominal effusion, and severe, generalized air‐space filling. Focal increased opacities were present in the peripheral lung, as were multiple pulmonary blebs and bullae. Echocardiographic findings were consistent with cor pulmonale and pulmonary hypertension. Bronchoscopic findings were consistent with chronic inflammation. Pulmonary alveolar proteinosis (PAP) was confirmed at necropsy. Pulmonary alveolar proteinosis is an interstitial lung disease that results in accumulation of phospholipoproteinaceous material and should be included as a differential diagnosis for dogs with these clinical and imaging characteristics.